How has COVID-19 social distancing impacted physical activity patterns? Data from the PAMPA cohort, Brazil - Eduardo L. Caputo; Natan Feter; Igor R. Doring; Jayne S. Leite; Júlia Cassuriaga; Airton J. Rombaldi; Marcelo C. da Silva; Felipe F. Reichert (Elsevier, 2021)
Objective: This study aimed to evaluate how social distancing measures affected physical activity (PA) patterns in adults from Rio Grande do Sul, Brazil. Methods: Participants were recruited from social and local media campaigns, contacts with private and public universities, as well as research personal contacts across the state. PA was assessed before (retrospectively) and during social distancing. Frequency (days per week) and time (minutes per day) were asked to those participants who practiced PA. Two PA variables were built to each time-frame (before and during social distancing): 1) any PA (yes/no question), and 2) sufficient PA (based on the 150 min/week cut-off point). Results: Overall, 2321 participants answered the questionnaire. Any and sufficient PA decreased from before to during social distancing (22.3% and 17.0%, respectively). A linear increase of activity during social distancing was observed in participants who practiced up to 400 min or less of PA per week before social distancing. Regarding associated factors, female, overweight/obese and diagnosed chronic disease participants were less likely to practice any or sufficient PA during social distancing when compared to the period before. Conclusion: PA practice (both any and sufficient) decreased in Southern Brazil in the first months of social distancing. Women, overweight/obese and chronic diseased participants showed a higher decrease in PA compared to other groups. Finally, those participants who practiced PA before social distancing were more likely to continue practicing during COVID-19 pandemic.